Digestible Lysine Requirements for Maintenance in the Starting Turkey - Brown, J.; Firman, J.D.; Sun, S.S.; Kamyab, A. (International Journal of Poultry Science, 2006)
Amino acid requirement data can be determined in multiple fashions. One method for determining amino acid requirement is through modeling. A portion of the data required for a comprehensive model is the maintenance requirement. The objective of these studies was to determine the digestible lysine requirement for maintenance in turkeys during the starter period. A low protein diet was formulated so that 8 different levels of lysine could be fed to young turkeys. Two experiments were conducted consisting of 8 treatments and 6 replicate pens of turkeys beginning at day 7. The maintenance requirements of lysine were 28.58 and 33.72 mg/bird/day in experiment 1 and experiment 2, respectively with an average requirement of 31.15 mg/bird/day. The requirements indicated by the two experiments did not agree completely, but the difference in predicted requirements was not large. This information, coupled with the amino acid requirements for growth, will allow for the construction of an effective model to predict amino acid requirements over a wide range of environment and physiological conditions.